2016
DOI: 10.2109/jcersj2.15308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical properties of Li<sub>4</sub>Ti<sub>5</sub>O<sub>12</sub>/C nano-powders by pulse jet spray pyrolysis

Abstract: Li 4 Ti 5 O 12 /C nano-powders were successfully synthesized at 500°C through the pulse jet spray pyrolysis with use of a citric acid aqueous solution. As-prepared Li 4 Ti 5 O 12 /C nano-particles had spherical and irregular shapes with an average size of 50 nm. Asprepared Li 4 Ti 5 O 12 /C nano-particles had a spinel phase with high crystallinity and a homogeneous chemical composition. The carbon content was 10 wt % in the Li 4 Ti 5 O 12 nano-powders. A 2032 type coin cell was used to examine electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[ 8 ] Many research achievements showed that electrodes consisting of nano‐particles exhibit higher capacity and cycling performance. [ 9–11 ] However, nanoparticles usually have low tap density which adds to the complexity of electrode production. Ultrafine electrode materials with high specific surface area tend to agglomerate at the surface of current collector and increase the contact resistance between collector and electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] Many research achievements showed that electrodes consisting of nano‐particles exhibit higher capacity and cycling performance. [ 9–11 ] However, nanoparticles usually have low tap density which adds to the complexity of electrode production. Ultrafine electrode materials with high specific surface area tend to agglomerate at the surface of current collector and increase the contact resistance between collector and electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐scale Li 4 Ti 5 O 12 is generally obtained by wet chemical methods, including hydrothermal/solvothermal methods, emulsion gel process, and spray drying. [ 11,16,17 ] The wet chemical methods require a large amount of solvents, such as water, ethanol, or citric acid, and metal‐organic compounds. Using organic solvents and metal precursors in large amounts not only releases carbon dioxide into the environment after high temperature calcinations, but also increases production costs.…”
Section: Introductionmentioning
confidence: 99%